Habitual water intake impacted the body composition of young male athletes in free-living conditions: a cross-sectional study - Zhang, Jianfen; Zhang, Na; Li, Yibin; He, Hairong; Song, Ge; Chen, Junying; Yan, Yi; Ma, Guansheng (Frontiers in Sports and Active Living, 2024)
The study aimed to explore the associations between water intake and body composition and differences of body composition in different water itake and hydration statuses among young male athletes. A cross-sectional study was conducted among 111 young male athletes in Beijing, China. Total drinking fluids (TDF) and water from food were assessed using a 7-day, 24-hour fluid intake record questionnaire and the duplicate portion method, respectively. The osmolality of 24hour urine and blood samples was tested. Body composition was measured using a bioelectrical impedance analyzer twice at 5-minute intervals. Participants were divided into two groups based on the recommendations of total water intake (TWI) and TDF in China, as well as into three groups based on 24-hour urine osmolality.Pearson's correlation coefficients were calculated to determine the relationship between water intake and body composition. Chi-square tests and Student's t-tests were used to compare differences. A total of 109 participants completed the study.